2016
DOI: 10.3758/s13420-016-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Extinction in multiple contexts: Effects on the rate of extinction and the strength of response recovery

Abstract: In two human predictive-learning experiments, we investigated the effects of extinction in multiple contexts on the rate of extinction and the strength of response recovery. In each experiment, participants initially received acquisition training with a target cue in one context, followed by extinction either in a different context (extinction in a single context) or in three different contexts (extinction in multiple contexts). The results of both experiments showed that conducting extinction in multiple cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As Sullivan et al () argued, the Nonsequential assessment of renewal reported herein aligns more closely to the contextual changes that clients experience during outpatient treatment for severe destructive behavior than does the standard, Sequential method for assessing renewal. A small but burgeoning literature has been devoted to mitigation of relapse in the face of contextual changes (e.g., Bernal‐Gamboa, Nieto, & Uengoer, ; Bustamante, Uengoer, Thorwart, & Lachnit, ; Kelley, Jimenez‐Gomez, Podlesnik, & Morgan, ). Unless these intervention strategies are assessed in the context of outpatient services for severe destructive behavior or other behavior disorders (as in the case of Kelley et al, ) or under the Nonsequential renewal assessment reported here, it remains to be seen whether those strategies would successfully mitigate renewal under the set of environmental/contingency changes in place during outpatient behavioral services.…”
Section: Discussionmentioning
confidence: 99%
“…As Sullivan et al () argued, the Nonsequential assessment of renewal reported herein aligns more closely to the contextual changes that clients experience during outpatient treatment for severe destructive behavior than does the standard, Sequential method for assessing renewal. A small but burgeoning literature has been devoted to mitigation of relapse in the face of contextual changes (e.g., Bernal‐Gamboa, Nieto, & Uengoer, ; Bustamante, Uengoer, Thorwart, & Lachnit, ; Kelley, Jimenez‐Gomez, Podlesnik, & Morgan, ). Unless these intervention strategies are assessed in the context of outpatient services for severe destructive behavior or other behavior disorders (as in the case of Kelley et al, ) or under the Nonsequential renewal assessment reported here, it remains to be seen whether those strategies would successfully mitigate renewal under the set of environmental/contingency changes in place during outpatient behavioral services.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have investigated other phenomena of context-related extinction learning using this paradigm of the predictive learning task - e.g. extinction in multiple contexts (Bustamante et al 2016 ; Glautier et al 2013 ) or differently composed contexts (Lucke et al 2014 ), as well as partial reinforcement and context switch effects (Abad et al 2009 ; Rosas and Callejas-Aguilera 2006 ). In imaging and pharmacological studies, the predictive learning task has been used to investigate areas active during extinction and renewal, the role of stress and of the dopaminergic and noradrenergic systems for extinction and renewal (Hamacher-Dang et al 2013 ; Kinner et al 2016 ; S. Lissek et al 2015a ; Lissek et al 2015b ; Lissek et al 2013 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a we compared light with heavy drinkers and in Experiment 2 we compared light with abstinent dependent drinkers. The computer task used has well-established methods and is typical of tasks used in the study of human Pavlovian learning [17,[23][24][25]. The task consists of a series of trials in which distinctive onscreen cues (CSs) and outcomes (USs) are presented.…”
Section: Methodsmentioning
confidence: 99%